2011
DOI: 10.1111/j.1420-9101.2011.02425.x
|View full text |Cite
|
Sign up to set email alerts
|

Sick ants become unsociable

Abstract: Parasites represent a severe threat to social insects, which form high‐density colonies of related individuals, and selection should favour host traits that reduce infection risk. Here, using a carpenter ant (Camponotus aethiops) and a generalist insect pathogenic fungus (Metarhizium brunneum), we show that infected ants radically change their behaviour over time to reduce the risk of colony infection. Infected individuals (i) performed less social interactions than their uninfected counterparts, (ii) did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
123
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 64 publications
(132 reference statements)
8
123
2
1
Order By: Relevance
“…If increased worker activity (outside of the nest) would increase the spreading success of the fungus, one may expect infected ants to exhibit a higher degree of out-of-nest activity (Bos et al 2012, sensu Hughes et al 2011. Where a host forages more outside and fights, this would have a positive effect on the spread of the fungus compared to the behaviour of a submissive host who stays inside the nest.…”
Section: Discussionmentioning
confidence: 99%
“…If increased worker activity (outside of the nest) would increase the spreading success of the fungus, one may expect infected ants to exhibit a higher degree of out-of-nest activity (Bos et al 2012, sensu Hughes et al 2011. Where a host forages more outside and fights, this would have a positive effect on the spread of the fungus compared to the behaviour of a submissive host who stays inside the nest.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, pathogen exposure leads to the complete exclusion of exposed individuals. For example, ants exposed to an entomopathogenic fungus voluntarily leave the nest, a behaviour known as 'self-removal' [48,58,59 ] (see [58,60] for a general effect of health condition on self-removal). Moreover, diseased individuals are sometimes actively excluded by their nestmates: in termites, nematode-infected individuals are walled in [14], whereas in the honeybee, infected workers are declined entrance [14] or dragged out of the hive [61 ].…”
Section: Spatial Segregationmentioning
confidence: 99%
“…In 1988, Hart 81 first argued that sickness behaviour is not a maladaptive response to infection but rather a coordinated behavioural strategy to promote host survival. A more recent hypothesis attributes sickness behaviour to altruism and kin selection 82 ; that is, sickness behaviour provides an evolutionary advantage to survival of the herd 83,84 . Interestingly, it has been reported that, if the infected host does not elicit overt sickness behaviour, they may increase their propensity to aggregate 85 .…”
Section: A Virus-versus-host Competitionmentioning
confidence: 99%